Premeditated Murder on Board While Searching for Shelter According to Human Rights - Arina Haqia; Arini Haqia (Yayasan Mentari Madani, 2023)
Premeditated murder is a crime against life stipulated in Article 340 of the Criminal Code. Premeditated murder is an act that stands alone with ordinary murder regulated in Article 338 of the Criminal Code. The provisions contained in the act of premeditated murder are a repetition of the murder act in Article 338 of the Criminal Code. The approach used in reviewing this research is the statutory approach (statute approach) and conceptual approach (conceptual approach). This research is legal (normative juridical) by understanding various sources. Primary is based on legislation, secondary is based on the study of books and journals, and the last is tertiary, based on dictionaries to find foreign languages that are difficult to understand